The prevalence and risk factors of lower back pain in emergency room nurses - Mikołajczyk, Edyta; Kaleta, Zofia; Janusz, Mariusz (Health Promotion & Physical Activity, 2017)
Aim of the study: To assess prevalence and risk factors of low back pain (LBP) in emergency room nurses in Krakow. Materials and methods: The study comprised 30 randomly selected full time emergency nurses aged 25-58. Their BMI was calculated and measurements of linear segmental lumbar spine flexion-extension motion were performed. The visual analogue scale (VAS) was used to assess the subjective LBP degree. The self-estimated physical disability caused by LBP was assessed by means of the Roland- Morris Low Back Pain and Disability Questionnaire (RMDQ), whereas physical activity by means of the International Physical Activity Questionnaire (IPAQ). The Spearman correlation coefficient was used to determine a linear association between variables involved in the research. Results: Statistically significant correlations between BMI, LBP and the level of disability as well as between the pain intensity and the time spent in a sitting position were revealed by RMDQ. Significant correlations between the self-estimated LBP and spinal flexion in the sagittal plane, lateral flexion to the right in the frontal plane and twist to the right in the transverse plane were found. Conclusions: Moderate LBP in emergency ward nurses, which is commonly observed, slightly decreased their quality of life. A high level of physical activity and limited range of flexion were discovered in the sagittal plane. Due to the existing correlations between BMI and LBP, between the degree of disability and the intensity of pain and the range of motion, it seems appropriate to include this occupational group in the back pain prevention programme.